Effect of selective IK, ACh inhibition by XAF‐1407 in an equine model of tachypacing‐induced persistent atrial fibrillation. (24th June 2020) - Fenner, Merle Friederike; Carstensen, Helena; Dalgas Nissen, Sarah; Melis Hesselkilde, Eva; Scott Lunddahl, Christine; Adler Hess Jensen, Maja; Loft‐Andersen, Ameli Victoria; Sattler, Stefan Michael; Platonov, Pyotr; El‐Haou, Said; Jackson, Claire; Tang, Raymond; et al.
Abstract : Background and Purpose: Inhibition of the G‐protein gated ACh‐activated inward rectifier potassium current, I K, ACh may be an effective atrial selective treatment strategy for atrial fibrillation (AF). Therefore, the anti‐arrhythmic and electrophysiological properties of a novel putatively potent and highly specific I K, ACh inhibitor, XAF‐1407 (3‐methyl‐1‐[5‐phenyl‐4‐[4‐(2‐pyrrolidin‐1‐ylethoxymethyl)‐1‐piperidyl]thieno[2, 3‐d]pyrimidin‐6‐yl]azetidin‐3‐ol), were characterised for the first time in vitro and investigated in horses with persistent AF. Experimental Approach: The pharmacological ion channel profile of XAF‐1407 was investigated using cell lines expressing relevant ion channels. In addition, eleven horses were implanted with implantable cardioverter defibrillators enabling atrial tachypacing into self‐sustained AF. The electrophysiological effects of XAF‐1407 were investigated after serial cardioversions over a period of 1 month. Cardioversion success, drug‐induced changes of atrial tissue refractoriness, and ventricular electrophysiology were assessed at baseline (day 0) and days 3, 5, 11, 17, and 29 after AF induction. Key Results: XAF‐1407 potently and selectively inhibited Kir 3.1/3.4 and Kir 3.4/3.4, underlying the I K, ACh current. XAF‐1407 treatment in horses prolonged atrial effective refractory period as well as decreased atrial fibrillatory rate significantly (~20%) and successfully cardioverted AF, although with a decreasing efficacy over time. XAF‐1407 shortened atrioventricular‐nodal refractoriness, without effect on QRS duration. QTc prolongation (4%) within 15 min of drug infusion was observed, however, without any evidence of ventricular arrhythmia. Conclusion and Implications: XAF‐1407 efficiently cardioverted sustained tachypacing‐induced AF of short duration in horses without notable side effects. This supports I K, ACh inhibition as a potentially safe treatment of paroxysmal AF in horses, suggesting potential clinical value for other species including humans. Abstract :